The Influence of Instrumental Music Alam Menyapa for Prenatal and Postnatal Patients at the Martha Friska Multatuli Hospital - Ronald Heriko Saragih; Junita Batubara; Happy Majesty Waruwu; Merdiani Gulo (Gondang: Jurnal Seni dan Budaya, 2023)
The research was a trial of instrumental music therapy on prenatal and postnatal patients at the Martha Friska Multatuli Hospital in Medan. The aim of this research is to be a solution to reduce pain and stress so that mothers who are about to give birth and after giving birth can feel relaxed. The tool used in the research is BmT (Music Box Therapy). Previously, BmT (Music Box Therapy) was tested on patients affected by drugs at the Mutiara Abadi Binjai Foundation (2019) and hypertension patients at the Medan Methodist Hospital (2021). The method used in the research was a quasi-experiment on four patients before and after giving birth. The BmT is designed to use two types of sensors, namely the MPX5050dp sensor as a blood pressure sensor and Galvanic Skin Resistance (GSR) as a sensor to measure the patient's skin conductivity level. One of the components of BmT is 16 pieces of instrumental music which are musical compositions by Prof. Junita Batubara, S.Sn., M.Sn., Ph.D.. The results of this trial show that the use of the instrumental music Alam Selamat, which is one of the therapeutic music in BmT, can reduce stress levels in mothers who are about to give birth and after giving birth.